Preferential attentional engagement drives attentional bias to snakes in Japanese macaques (Macaca fuscata) and humans (Homo sapiens) - Masataka, Nobuo (Sci Rep, 2018)
In humans, attentional biases have been shown to negative (dangerous animals, physical threat) and positive (high caloric food, alcohol) stimuli. However, it is not clear whether these attentional biases reflect on stimulus driven, bottom up, or goal driven, top down, attentional processes. Here we show that, like humans, Japanese macaques show an attentional bias to snakes in a dot probe task (Experiment 1). Moreover, this attentional bias reflects on bottom up driven, preferential engagement of attention by snake images (Experiment 2a), a finding that was replicated in a study that used the same methodology in humans (Experiment 2b). These results are consistent with the notion that attentional bias to snakes reflects on an evolutionarily old, stimulus driven threat detection mechanism which is found in both species.